Ignition of combustible gases by radiative heating of inert particles - Baek, Seung Wook (Combustion and flame, 1994)
In this work the thermal ignition of a two-phase mixture, using a suspension comprising inert particles and hydrogen/air in slab geometry, is to be quantitatively and qualitatively analyzed. Whereas the hydrogen/air is assumed to be transparent to radiation, the solid particles are considered to actively absorbed and emit the radiation. A two-phase mixture of inert particles and hydrogen/air is contained between two transparent parallel walls. At one side, the mixture is subject to an external high temperature source of radiation. The main assumptions used in the following analysis can be summarized as follows: (1) The system is one dimensional and open. Therefore the gas expansion is neglected. (2) The uniform mixture of inert particles and hydrogen/air remains quiescent. (3) Occupied volume by particle is negligible compared with the gas suspension volume. (4) Only the particles are supposed to absorb and emit the radiation; the gas mixture is transparent to radiation.